The Lymphatic Pump Technique for the Treatment of the Lower Limb Lymphedema - Bergna A.; Panigada L.; Benussi F.; Buffone F.; Caruana C.; Castrignano M.; Ciancone E.; Cazzaniga F; Sotgiu A.; Bressan V.; Bressan L.C; Solimene U. (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Lymphedema is a condition occurring when the lymphatic system fails to efficiently transport the lymph, thus creating a fluid accumulation in the interstitial space. As of today, the rehabilitation treatment for lymphedema relies on the principles of Complete Decongestive Therapy (CDT), a series of treatments designed to favor the reabsorption of the lymph by the lymphatic system and to restore the functionality of the affected limb. From an osteopathic point of view, interesting results have been obtained through Lymphatic Pump Technique (LPT), a series of oscillatory techniques applied to different areas of the body such as chest, abdomen and feet. A few LPT studies on animals have shown a significant improvement not only in the lymphatic system efficiency (an increase of 271% in lymph flow) but also in the immune system.